THE EFFECTS OF STOCKING DENSITY, WATER EXCHANGE RATE, FEEDING FREQUENCY AND GRADING ON SIZE HIERARCHY DEVELOPMENT IN JUVENILE NILE TILAPIA, OREOCHROMIS NILOTICUS L. - Yousif, O. M. (Emirates Journal of Food and Agriculture, 2017)
The effects of stocking density and water exchange rate on size variation of juvenileOreochromis niloticus were studied. The fish subjected to the lowest stocking (0.5/L) and highest water exchange rate (20 times/hr) achieved the best (p < 0.05) final body weight. Exposure of fish to the highest stocking density (2/L) and lowest water exchange rate (5 times/hr) resulted in the poorest (p < 0.05) final body weight. The coefficient of variation of body weights of individuals subjected to the lowest and intermediate water exchange rates (5 and 10 times/hr, respectively) increased withincreasing stocking density (from 0.5 to 2 fish/L). Fish subjected to the highest water exchange rate (20/Times/hr) did not show a similar consistent trend. Water-borne stresses compounded by those resulting from crowding and/or competition for food was suggested as the primary causes of size variation within treatments. Manipulation of water exchange rates to improve water quality and hence minimize the adverse effects of crowding was suggested. The influences of stocking density,feeding frequency and grading on size hierarchy development were also investigated. Stocking density and feeding frequency had an effect on size hierarchy development. The coefficient of variation of body weights of fish fed least frequently (2 times/day) increased with increasing stocking density (from 0.5 to 2 fish/L). The two groups fed 3 and 4 times/day showed an inverse relationship. Size hierarchy in the homogeneous size distributions was observed to reestablish within two weeks and increased steadily thereafter, whilst in the non-graded group (mixed group), a steadyreduction in size variation was noted with time.